Effects of intravenous zoledronic acid plus subcutaneous teriparatide (rhPTH(1-34)) in postmenopausal osteoporosis - Cosman, Felicia; Eriksen, Erik Fink; Recknor, Chris; Miller, Paul D; Guañabens, Núria; Kasperk, Christian; Papanastasiou, Philemon; Readie, Aimee; Rao, Hanumantha; Gasser, Jürg A; Bucci-Rechtweg, Christina; Boonen, Steven (Journal of bone and mineral research, 2011)
Clinical data suggest concomitant therapy with bisphosphonates and parathyroid hormone (PTH) may blunt the anabolic effect of PTH; rodent models suggest that infrequently administered bisphosphonates may interact differently. To evaluate the effects of combination therapy with an intravenous infusion of zoledronic acid 5 mg and daily subcutaneous recombinant human (rh)PTH(1-34) (teriparatide) 20 µg versus either agent alone on bone mineral density (BMD) and bone turnover markers, we conducted a 1-year multicenter, multinational, randomized, partial double-blinded, controlled trial. 412 postmenopausal women with osteoporosis (mean age 65 ± 9 years) were randomized to a single infusion of zoledronic acid 5 mg plus daily subcutaneous teriparatide 20 µg (n = 137), zoledronic acid alone (n = 137), or teriparatide alone (n = 138). The primary endpoint was percentage increase in lumbar spine BMD (assessed by dual-energy X-ray absorptiometry [DXA]) at 52 weeks versus baseline. Secondary endpoints included change in BMD at the spine at earlier time points and at the total hip, trochanter, and femoral neck at all time points. At week 52, lumbar spine BMD had increased 7.5%, 7.0%, and 4.4% in the combination, teriparatide, and zoledronic acid groups, respectively (p < .001 for combination and teriparatide versus zoledronic acid). In the combination group, spine BMD increased more rapidly than with either agent alone (p < .001 versus both teriparatide and zoledronic acid at 13 and 26 weeks). Combination therapy increased total-hip BMD more than teriparatide alone at all times (all p < .01) and more than zoledronic acid at 13 weeks (p < .05), with final 52-week increments of 2.3%, 1.1%, and 2.2% in the combination, teriparatide, and zoledronic acid groups, respectively. With combination therapy, bone formation (assessed by serum N-terminal propeptide of type I collagen [PINP]) increased from 0 to 4 weeks, declined minimally from 4 to 8 weeks, and then rose throughout the trial, with levels above baseline from 6 to 12 months. Bone resorption (assessed by serum β-C-telopeptide of type I collagen [β-CTX]) was markedly reduced with combination therapy from 0 to 8 weeks (a reduction of similar magnitude to that seen with zoledronic acid alone), followed by a gradual increase after week 8, with levels remaining above baseline for the latter half of the year. Levels for both markers were significantly lower with combination therapy versus teriparatide alone (p < .002). Limitations of the study included its short duration, lack of endpoints beyond DXA-based BMD (e.g., quantitative computed tomography and finite-element modeling for bone strength), lack of teriparatide placebo, and insufficient power for fracture outcomes. We conclude that while teriparatide increases spine BMD more than zoledronic acid and zoledronic acid increases hip BMD more than teriparatide, combination therapy provides the largest, most rapid increments when both spine and hip sites are considered. © 2011 American Society for Bone and Mineral Research.
First published: 02 September 2010
Gesehen am 13.04.2022